2016
DOI: 10.1002/ddr.21346
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Diurnal Rodents in the Research of Depression

Abstract: Preclinical Research Most neuropsychiatric research, including that related to the circadian system, is performed using nocturnal animals, mainly laboratory mice and rats. Mood disorders are known to be associated with circadian rhythm abnormalities, but the mechanisms by which circadian rhythm disruptions interact with depression remain unclear. As the circadian system of diurnal and nocturnal mammals differs, we previously suggested that the utilization of diurnal animal models may be advantageous for unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 86 publications
(113 reference statements)
0
32
0
Order By: Relevance
“…Herein we discuss research findings relating to the proposed Circadian Syndrome risk components and comorbidities (Table 2). Hypertension Lack of nocturnal decline in blood pressure [30,62] High blood pressure [22] Lipids Disrupted lipid homeostasis [69,70] Obesity Disrupted diurnal rhythms in the white adipose tissue transcriptome [73] Obesity [22] Blood glucose levels Disrupted daily rhythms in blood glucose levels and glucose intolerance [17,21,75] Disrupted daily rhythms in blood glucose levels and glucose intolerance [22] Fatty liver Disrupted triglyceride accumulation, inflammation, oxidative stress and mitochondrial dysfunction [29] Depression Circadian disruption increases the incidences of depression [86,87] Circadian disruption increases the incidences of depression [22,83,84,[105][106][107][108][109][110] Sleep disturbances Circadian disturbances result in sleep loss and mistimed sleep [56,97] Proposing a Circadian Syndrome: Cardiovascular-related components Circadian oscillations have been reported for both physiological CVD regulation including heart rate and blood pressure [57], for cardiac disorders including arrythmias [58,59], and there is circadian variation in frequency of onset of myocardial infarction and sudden cardiac death [19,60].…”
Section: Circadian Disruption and Associations With Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein we discuss research findings relating to the proposed Circadian Syndrome risk components and comorbidities (Table 2). Hypertension Lack of nocturnal decline in blood pressure [30,62] High blood pressure [22] Lipids Disrupted lipid homeostasis [69,70] Obesity Disrupted diurnal rhythms in the white adipose tissue transcriptome [73] Obesity [22] Blood glucose levels Disrupted daily rhythms in blood glucose levels and glucose intolerance [17,21,75] Disrupted daily rhythms in blood glucose levels and glucose intolerance [22] Fatty liver Disrupted triglyceride accumulation, inflammation, oxidative stress and mitochondrial dysfunction [29] Depression Circadian disruption increases the incidences of depression [86,87] Circadian disruption increases the incidences of depression [22,83,84,[105][106][107][108][109][110] Sleep disturbances Circadian disturbances result in sleep loss and mistimed sleep [56,97] Proposing a Circadian Syndrome: Cardiovascular-related components Circadian oscillations have been reported for both physiological CVD regulation including heart rate and blood pressure [57], for cardiac disorders including arrythmias [58,59], and there is circadian variation in frequency of onset of myocardial infarction and sudden cardiac death [19,60].…”
Section: Circadian Disruption and Associations With Risk Factorsmentioning
confidence: 99%
“…Depression is a well-established comorbidity associated with T2DM [79][80][81][82]. Nearly all patients with affective disorders including depression show significant disruptions in circadian rhythms [83][84][85][86][87].…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here it is to consider that the manipulations have been mainly conducted in nocturnal animals and results might not be comparable to mechanisms in diurnal humans (Challet 2007). Using diurnal rodent animal models could be beneficial in this field of research (Ashkenazy et al 2009; Bilu et al 2016; Einat et al 2006; Leach et al 2013). Nevertheless, effects are quite robust as various disruptions of one gene (i.e., Clock ) as well as targeting related pathways or environmentally influence sleeping behavior result in similar effects (McClung et al 2005; Mukherjee et al 2010; Prickaerts et al 2006; Roybal et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the current experiment, environmental enrichment included materials that enabled the building of a somewhat shaded nest by the mice. (3) It had been suggested that the sensitivity to light manipulations is higher and more consistent in diurnal animals compared with nocturnal ones [27][28][29], whereas the current study used nocturnal mice.…”
Section: Discussionmentioning
confidence: 82%